2011
DOI: 10.3945/jn.111.141960
|View full text |Cite
|
Sign up to set email alerts
|

Transcobalamin Polymorphism 67A->G, but Not 776C->G, Affects Serum Holotranscobalamin in a Cohort of Healthy Middle-Aged Men and Women

Abstract: Two polymorphic variants in the gene coding for transcobalamin II (TCN2), TCN2 776C- > G and TCN2 67A- > G, may alter serum holotranscobalamin (holoTC), which in turn may affect cellular uptake of cobalamin (Cbl) and thereby Cbl status indicators. We studied the effects of TCN2 776C- > G and TCN2 67A- > G on blood concentrations of holoTC, Cbl, methylmalonic acid (MMA), and total homocysteine (tHcy) in 2411 individuals (50-64 y) that had been selected on the basis of these TCN2 genotypes from 10601 Norwegian i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
1
22
1
Order By: Relevance
“…The p.P259R variant has been reported to have no effect [ 25 ] or to be related to only moderately elevated levels of TC [ 26 -28 ], levels that are much lower than observed in our patients. Thus, any genetic cause was unlikely to explain the observed elevation in TC.…”
Section: Discussioncontrasting
confidence: 82%
“…The p.P259R variant has been reported to have no effect [ 25 ] or to be related to only moderately elevated levels of TC [ 26 -28 ], levels that are much lower than observed in our patients. Thus, any genetic cause was unlikely to explain the observed elevation in TC.…”
Section: Discussioncontrasting
confidence: 82%
“…This suggests [36][37][38] in addition to increased MMA [39] and Hcy concentrations [37,40]. Previous studies, however, did not find an association between this polymorphism and either holotranscolbalamin [41] or Hcy [38,42]. Furthermore, an increase in Hcy concentration was shown to be associated with the heterozygous TCN2 776 CG genotype when compared to the homozygous genotypes [36].…”
Section: Discussionmentioning
confidence: 78%
“…Even though direct proof is lacking, megalin is highly expressed in embryonic tissue and is a likely candidate receptor for TC-Cbl during fetal development. While there is no clear consensus on the association of maternal low Cbl status and birth defects, most studies have shown some albeit, weak correlation with low Cbl status and elevated matabolites such as HCY and MMA (52-55). A stronger correlation was observed with a decrease in the level of maternal holo TC with increased risk for birth defects.…”
Section: Introductionmentioning
confidence: 99%